Fracture toughness of multilayer pipes - Nezbedova, E.; Fiedler, L.; Majer, Z.; Vlach, B.; Knesl, Z. (Проблемы прочности, 2008)
Multilayer pipes composed of various materials improve partially the properties of a pipe system and are frequently used in service. To estimate the lifetime of these pipes the basic fracture parameters have to be measured. In the contribution a new approach to this estimation is presented. Special type of a C-shaped inhomogeneousfracture mechanics specimen machined directlyfrom a pipe has been proposed, numerically analyzed and tested. The corresponding K values are calculated by FEM and fracture toughness values of HDPE pipes material are obtained.